Regulation and planning - Tatar, Mehtap; Mollahaliloğlu, Salih; Şahin, Bayram; Aydın, Sabahattin; Maresso, Anna; Hernández-Quevedo, Cristina (WHO Regional Office for Europe, 2011)
This chapter outlines the principles and practice of regulation and planning in the Turkish health care system. Table 4.1 outlines the main legislative arrangements upon which the health care system is based. As can be seen from Table 4.1, some of the basic legislation used in health care is quite old; however, the dates mentioned are the acceptance dates of the laws and each has undergone several revisions over time, reflecting changes in the health care environment. In the Turkish health care system, decrees and directives also play an important role. Laws create the main legislative framework, and successive decrees and directives may be issued for the purposes of implementation.
Keywords: Delivery Of Health Care; Evaluation Studies; Financing, Health; Health Care Reform; Health System Plans – Organization and Administration; Turkey